Parental mental health literacy : investigating parental knowledge of child mental health disorders and mental health resources available for children - Dagný Björt Jakobsdóttir 2000- (2022)
Parental mental health literacy is defined as a parents´ knowledge of mental health disorders concerning recognizing, preventing, and managing mental health disorders that children are at risk of developing. This research explores how well parents can identify mental health disorders and the resources available for children with mental health disorders. Furthermore, it was investigated what variables significantly influenced parental mental health literacy. The inclusion criteria for the experiment were to be a parent of a child under the age of 18, and participants themselves had to be over 18 years old. All participants were Icelandic-speaking parents. The participants were recruited on various online social media platforms and through email. A questionnaire was designed to measure parental knowledge of mental health disorders and resources, as well as other background information. Regression analysis, as well as co and means between groups, we utilized to analyze results. The results showed that gender and self-reported knowledge of disorders were predictors of knowledge of disorders. How many children parents had and stigma were predictors of knowledge of resources. More research regarding parental mental health literacy in Iceland is needed to gain a clear insight into the knowledge Icelandic parents hold. Child mental health should be a more pressing issue in the present discussion regarding mental health as well as the overall health of children. Keywords: parental mental health literacy, child mental health disorders, mental health resources, mental health literacy Geðheilbrigðis læsi íslenskra foreldra er skilgreint sem þekking foreldris á geðheilbrigðisröskunum, í því felst að þekkja, koma auga á og geta þá frekar komið í veg fyrir geðheilbrigðisröskunum sem börn gætu þróað með sér. Þessi rannsókn var gerð til að kanna frekar hversu vel foreldrar komi auga á einkenni geðheilbriðisraskana og hversu vel þau þekki þau úrræði sem í boði eru.Ennfremur var kannað hvaða breytur höfðu marktæk áhrif á ...